2010
DOI: 10.3199/iscb.5.37
|View full text |Cite
|
Sign up to set email alerts
|

Karyomorphological studies in Mucuna of India

Abstract: Mucuna Adans. is a large genus with more than 150 species of annual and perennial legumes of pantropical distribution. Despite considerable economic importance of some of its species, almost no work has been done on their cytogenetic characterization in any part of World. In this paper, we have presented a fi rst report on karyomorphological analysis in four Indian species viz., Mucuna atropurpurea, Mucuna monosperma, Mucuna nigricans and Mucuna pruriens bringing out diploid number for M. atropurpurea and kary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…Mucuna has very low % of polyploidy. Earlier workers reported diploid chromosome number of 2n = 22 in M. pruriens, (Bairiganjan andPatnaik 1989), M. monosperma (Thuvan 1975), in M. atropurpurea (Jaheer and Sathyanarayana 2010) and M. nigricans (Kumari and Bir 1990) and in our present cytological investigation for diploid chromosome number of M. sanjappae and M. macrocarpa 2n = 22 was observed. For the determination of the THCL of papilionaceous legume the chromosome size is more important and is the real determinant rather than chromosome number Bir 1985, 1989).…”
Section: Resultssupporting
confidence: 56%
“…Mucuna has very low % of polyploidy. Earlier workers reported diploid chromosome number of 2n = 22 in M. pruriens, (Bairiganjan andPatnaik 1989), M. monosperma (Thuvan 1975), in M. atropurpurea (Jaheer and Sathyanarayana 2010) and M. nigricans (Kumari and Bir 1990) and in our present cytological investigation for diploid chromosome number of M. sanjappae and M. macrocarpa 2n = 22 was observed. For the determination of the THCL of papilionaceous legume the chromosome size is more important and is the real determinant rather than chromosome number Bir 1985, 1989).…”
Section: Resultssupporting
confidence: 56%
“…Chromosomal studies even in genus Mucuna suggests x = 11 as the base number even though x = 14 is reported in Mucuna gigantea and Mucuna benettii (Sastrapradja et al, 1974; Jaheer and Sathyanarayana, 2010). So far, karyotype descriptions are available only for Mucuna atropurpurea, Mucuna monosperma, Mucuna nigricans and M. pruriens (Agostini et al , 2009; Jaheer and Sathyanarayana, 2010). Recently our group completed karyotyping of two other Indian species viz., Mucuna sempervirens, Mucuna bracteata .…”
Section: Karyotype and Phylogenetic Analysismentioning
confidence: 99%
“…Conservation of basic chromosome number x = 11 is one of the prevailing features in Phaseoloid legumes. Chromosomal studies even in genus Mucuna suggests x = 11 as the base number even though x = 14 is reported in Mucuna gigantea and Mucuna benettii (Sastrapradja et al, 1974;Jaheer and Sathyanarayana, 2010). So far, karyotype descriptions are available only for Mucuna atropurpurea, Mucuna monosperma, Mucuna nigricans and M. pruriens (Agostini et al, 2009;Jaheer and Sathyanarayana, 2010).…”
Section: Karyotype and Phylogenetic Analysismentioning
confidence: 99%
“…temperature. Root tips (about five mm in length) of three-to four-day old seedlings were 10 a.m. Root tips were treated and stained with aceto-carmine and ferri-acetate, following the procedure ofJaheer et al (2010). Mitotic metaphase figures were examined by light microscopy at 15 x 100 magnification (Leitz Dialux 20, Munich, Germany).…”
mentioning
confidence: 99%